Disclosure Of Hiv Status To Children Living With Hiv: National Clinical Approach And Psychosocial Support In The Context Of Uzbekistan (Eurasian Journal of Learning and Academic Teaching, 2026)
This article analyzes the medical, psychological, and legal aspects of disclosing HIV status to children living with HIV based on the healthcare system and national legislation of the Republic of Uzbekistan. The study highlights the stages of HIV status disclosure, multidisciplinary approaches, cooperation with parents, age-related and psychological characteristics of children, as well as psychosocial adaptation after disclosure. In addition, practical recommendations aimed at preventing discrimination, maintaining medical confidentiality, and protecting children’s rights in Uzbekistan are presented